Analisis Rasio Kinerja Keuangan Pada PT. Bank SULUTGO - Rawung, Scarlet E.; Rogahang, Joula J.; Mangindaan, Joanne V. (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
Research on using to find out and analyze financial performance at PT Bank-PLACES to GO. In this current era increasingly many companies appear and also being so tight, so from that company (bank) earnings should improve in order to be able to compete. The focus in this study is on the financial statements of the year 2015, 2016, and 2017, with financial ratios i.e. ratio of profitability, liquidity ratios, and ratios of the banking capital. While the source of the data used in this research is secondary data in the form of banking financial reports document from the year 2015 to 2017 are on acquire from webside https://www.banksulutgo.co.id . Results of the study showed a ratio of profitability have good financial kenerja, capital ratio and likuditas ratio also has a good financial performance, though in year 2015 to 2017 rising and decline but the financial performance the bank achieve not FLAMMABLE under standard BI BI standards but so can still in good financial ratio tells me. Therefore, PT. Bank SULUTGO should further improve the financial performance of a maximum in the next year.